Prevalence of metabolic syndrome and changes in body composition, physical fitness and cardiovascular risk factors during military service - Mikkola, I. (Ilona) (Oulun yliopisto, 2011)
Abstract Metabolic syndrome (MetS) is a cluster of obesity-related cardiometabolic risk factors. It predicts the development of cardiovascular disease and type 2 diabetes, which are major public health concerns. Visceral obesity and insulin resistance are the predominant underlying factors of MetS, other diagnostic components being elevated blood pressure, high triglycerides, and low HDL-cholesterol. The most important treatment of MetS is through lifestyle changes. There are limited data concerning the prevalence of MetS among young populations. Furthermore, even though the effects of physical activity on MetS components are well established at an individual basis and in some subpopulations, large population-based data about associations of young men’s fitness and MetS-related cardiometabolic risk factor changes are warranted. In Finland, military service is compulsory for males. In 2005, 1,160 young men (mean age 19.2 years, range 18–28 years) were followed throughout their military service (6–12 months) in the Sodankylä Jaeger Brigade. The military service period includes high amounts of physical exercise, but no dietary restrictions. Physical fitness, anthropometrics, body composition, and cardiometabolic risk factors were assessed at the beginning and at the end of military service. Among the entire study population, the prevalence of MetS was 3.5–6.8 %, depending on the definition used, and increased in parallel with an increasing body mass index. On the average, the military training period resulted in a decrease in body weight and amount of fat tissue, especially visceral fat, and improved physical fitness. Body composition and fitness improvements were more pronounced in overweight and obese service men. Beneficial changes in body composition and related cardiovascular risk factor improvements were associated with increased physical fitness, especially aerobic fitness. This study indicates that an improvement in physical fitness is related to improvements in body fat distribution and cardiovascular ...